MECHANISM OF INFECTION Spodoptera litura Nucleopolyhedrosis Multiple Virus (SpltMNPV) ON MIDGUT EPITHELIAL CELL ARMY WORM (Spodoptera litura) Observed by TEM - Mahanani Tri Asri; Siti Rasminah Chaelani; Bambang Tri Rahardjo; Sutiman Bambang Sumitro (AGRIVITA Journal of Agricultural Science, 2013)
Spodoptera litura is one of  agricultural crop pests. They are resistant to chemical insecticides. One of arternate biological control is Spodoptera litura Nucleopolyhedrosis Multiple Virus (SpltMNPV) Penelitian ini dilakukan untuk mengetahui bagaimana mekanisme SpLtMNPV dalam menginfeksi sel epithel midgut larva S. The research was conducted to determine how SpltMNPV infected midgut epithelial cells of S. litura secara in vitro . litura larvae in vitro.  The mechanism of infection was observed by a transmission electron microscopy (TEM).  The result of this observation showed that infecting midgut cell by  SpltMNPV involved 5 phases, they are, 1) the attachment of  SpltMNPV at the membrane of suitable host, 2) the penetration, formation of channels and release of protein envelope, 3) the biosynthesis of virus components in the cell nucleus, 4) the assembling of virus components, and 5) the releasing of MNPV/multiplenucleocapsid through budding. Keywords: mechanisms of infection, Spodoptera litura multiple nucleopolyhedrosis virus, midgut army worm larvae cells.